Nutritional Support for Critically Ill Patients (Review) - Igor N. Pasechnik (Общая реаниматология)
Hospital mortality in critical illness has decreased over the last decade. At the same time, there has been an increase in the number of patients diagnosed with post-intensive care syndrome (PIT-syndrome) which reduces the life quality after discharge. One of the most important components preventing the development of PIT syndrome is nutritional support.The aim of the review is to highlight the need for a differentiated approach to nutritional support of critically ill patients during their treatment and rehabilitation. Among more than 200 primary sources of literature from various databases (Scopus, Web of science, RINC, etc.), 82 sources mainly published in the last 5 years were selected for review. Earlier publications maintaining clinical relevance were also included into the analysis. The review presents data on real practice of nutritional support in critically ill patients. In most cases, the risk of nutritional deficiencies is not assessed before treatment, and protein and energy requirements are not fully met. The algorithm of nutritional support is provided based on the phases of critical illness.Conclusion. Contemporary approaches to the nutrient and energy provision to critically ill patients suggest the differentiated nutritive support prescription depending on the disease stage. The emphasis is made on gradual achievement of target values of protein and energy provision, priority of enteral administration of nutrients, continuity in nutritional support between departments, as well as hospital and outpatient treatment periods. This approach allows both optimization of medical care for this extremely challenging category of patients and a reduction in the severity and duration of the PIT syndrome.